Effects of Respiratory Rate on Heart Rate Variability in Neurologic Outpatients with Epilepsies or Migraine: A Preliminary Study - Druschky, Katrin; Lorenz, Jürgen; Druschky, Achim (Medical Principles and Practice, 2019)
Background: Variation of spontaneous respiratory rates and influences of spontaneous and paced breathing rates on heart rate variability (HRV) were assessed in patients with epilepsy or migraine, and HRV parameters were compared between the groups. Materials and Methods: Thirty neurologic outpatients, 16 diagnosed with epilepsies and 14 with migraine, were included. Autonomic testing consisted of short-term HRV, the deep breathing test (DBT), and measurement of HRV at systematically changed breathing rates (paced breathing, 5-18 breaths per minute, bpm). Results: Spontaneous respiratory rate during short-term HRV varied from 9 to 23 bpm in the epileptic group and from 5 to 21 bpm in migraine patients and was significantly and negatively correlated with SD of all normal RR intervals (SDNN) and total power (TP) in epileptic patients but not in migraine patients. Paced breathing rate had a significant effect on all HRV parameters assessed in both groups. HRV (SD1, SDNN, TP) and DBT (E-I, SD1, SDNN) parameters were significantly lower in the epileptic group. Group differences were significantly greater during slow compared to fast breathing. Conclusions: An important and new finding is the wide variation of spontaneous respiratory rate in both groups, along with the significant negative correlation with the assessed HRV parameters. The reduction of HRV during slow breathing in epileptic patients may indicate a diminished cardiorespiratory coupling caused by a probable loss of sensitivity within the cardiovagal brainstem circuitry.
CRIS-Team Scopus Importer:2019-12-20

Psychopharmacological Treatment of Schizophrenia Over Time in 30 908 Inpatients: Data From the AMSP Study - Toto, Sermin; Grohmann, Renate; Bleich, Stefan; Frieling, Helge; Maier, Hannah B.; Greil, Waldemar; Cordes, Joachim; Schmidt-Kraepelin, Christian; Kasper, Siegfried; Stübner, Susanne; Degner, Detlef; Druschky, Katrin; et al. (International Journal of Neuropsychopharmacology, 2019)
BACKGROUND: Psychotropic drugs are the cornerstone of schizophrenia treatment, often requiring lifelong treatment. Data on pharmacotherapy in inpatient settings are lacking. METHODS: Prescription data of schizophrenic inpatients within the time period 2000-2015 were obtained from the database of the Drug Safety Program in Psychiatry (AMSP). Data were collected at 2 index dates per year; the prescription patterns and changes over time were analyzed. RESULTS: Among 30 908 inpatients (mean age 41.6 years, 57.8% males), the drug classes administered most often were antipsychotics (94.8%), tranquilizers (32%), antidepressants (16.5%), antiparkinsonians (16%), anticonvulsants (14.1%), hypnotics (8.1%), and lithium (2.1%). The use of second-generation antipsychotics significantly increased from 62.8% in 2000 to 88.9% in 2015 (P < .001), whereas the prescription of first-generation antipsychotics decreased from 46.6% in 2000 to 24.7% in 2015 (P < .001). The administration of long-acting injectable antipsychotics decreased from 15.2% in 2000 to 11.7% in 2015 (P = .006). Clopazine was the most often used antipsychotic, having been used for 21.3% of all patients. Polypharmacy rates (≥5 drugs) increased from 19% in 2000 to 26.5% in 2015. Psychiatric polypharmacy (≥3 psychotropic drugs) was present in 44.7% of patients. CONCLUSIONS: Combinations of antipsychotics and augmentation therapies with other drug classes are frequently prescribed for schizophrenic patients. Though treatment resistance and unsatisfactory functional outcomes reflect clinical necessity, further prospective studies are needed on real-world prescription patterns in schizophrenia to evaluate the efficacy and safety of this common practice.
CRIS-Team Scopus Importer:2019-10-01
Keywords: AMSP; antipsychotics; pharmacotherapy; prescription; schizophrenia

Seizure rates under treatment with antipsychotic drugs: Data from the AMSP project - Druschky, Katrin; Bleich, Stefan; Grohmann, Renate; Engel, Rolf R.; Neyazi, Alexandra; Stuebner, Susanne; Toto, Sermin (World Journal of Biological Psychiatry, 2019)
Objectives: The study aimed to assess seizure rates related to different antipsychotic drugs (APDs) in a clinical setting using data from the drug safety programme Arzneimittelsicherheit in der Psychiatrie (AMSP). Methods: Psychotropic drug use data and reports of APD-related seizures were collected in 89 psychiatric hospitals in Austria, Germany and Switzerland from 1993 to 2015. Results: Of 475,096 patients under surveillance, 320,383 patients were treated with APDs for the main indications of schizophrenic disorders, mood disorders and organic disorders. A total of 144 APD-related tonic clonic seizures were identified (0.04%). The butyrophenones ranked slightly lower (0.03%) compared to the phenothiazines, thioxanthenes and second-generation APDs (0.05% each). No significant differences were observed when comparing first- and second-generation APDs. Clozapine was related to the highest seizure rate (0.18%). In 107 cases (74.3%), more than one drug was considered responsible for seizure induction. With the exception of clozapine, seizures imputed to a single APD were in the clear minority. Seizure rates under the combinations of APDs with tricyclic antidepressants or lithium, as well as under triple combinations of APDs, were increased approximately two-fold. Young age (<= 30 years), the male gender, and diagnosis of schizophrenic disorder were associated with significantly higher seizure rates (P < 0.05). Conclusions: Closely reflecting daily clinical practice, the present results provide supplementary information regarding APD therapy for patients not only at risk for seizures but also seizure-unaffected psychiatric inpatients.
CRIS-Team WoS Importer:2020-02-11

Severe drug-induced liver injury in patients under treatment with antipsychotic drugs: Data from the AMSP study - Druschky, Katrin; Toto, Sermin; Bleich, Stefan; Baumgaertner, Jessica; Engel, Rolf R.; Grohmann, Renate; Maier, Hannah B.; Neyazi, Alexandra; Rudolph, Yannick J.; Ruether, Eckart; Schwoerer, Harald; Seifert, Johanna; et al. (World Journal of Biological Psychiatry, 2020)
Objectives Drug-induced liver injury (DILI) has been associated with various antipsychotic drugs (APDs). Comparative studies between individual APDs are largely not available. Methods Antipsychotic drug utilisation data and reports of severe antipsychotic DILI were assessed by using data from an observational pharmacovigilance programme-Arzneimittelsicherheit in der Psychiatrie (AMSP)-during the period 1993-2016. Results Of the 333,175 patients treated with APDs, a total of 246 (0.07%) events of severe DILI were identified. Phenothiazines were associated with significantly higher rates of severe DILI (0.03%, 95% CI = 0.02-0.04) than thioxanthenes (0.01%, 95% CI = 0.00-0.02) or butyrophenones (0.01%, 95% CI = 0.00-0.01). Among individual drugs, olanzapine (0.12%, 95% CI = 0.10-0.16), perazine (0.09%, 95% CI = 0.05-0.15) and clozapine (0.09%, 95% CI = 0.10-0.12 ranked highest. In 78 cases (31.7%), combination therapies with antipsychotic and antidepressant drugs or with two or more APDs were considered responsible. Male sex and a diagnosis of mania were associated with significantly higher rates of severe DILI while older patients (>= 65 years old) were significantly less often affected. Conclusions In the present analysis of a representative psychiatric inpatient cohort, olanzapine, perazine, and clozapine were the most common individual APDs associated with severe DILI.
CRIS-Team WoS Importer:2020-10-09

Severe hair loss associated with psychotropic drugs in psychiatric inpatients-Data from an observational pharmacovigilance program in German-speaking countries - Druschky, Katrin; Bleich, Stefan; Grohmann, Renate; Burda, Katharina; Frieling, Helge; Hillemacher, Thomas; Neyazi, Alexandra; Stuebner, Susanne; Toto, Sermin (European Psychiatry, 2018)
BACKGROUND: The study aimed to investigate severe hair loss related to psychotropic drugs (PDs) by using data from the drug safety programme Arzneimittelsicherheit in der Psychiatrie (AMSP). METHODS: Data on PD utilization and reports of severe PD-related hair loss were collected in 83 psychiatric hospitals in Austria, Germany and Switzerland during the period 1993-2013. RESULTS: Out of 432,215 patients under surveillance, 404,009 patients were treated with PDs for the main indications of depression, schizophrenic disorder, neurosis, mania, and organic psychosis. Severe hair loss related to PD treatment was reported in 43 cases (0.01%). The rates of hair loss under antipsychotic drugs were slightly lower than the mean rates of all PDs and antidepressant drugs. Valproic acid was related to the highest risk. In 6 of the 43 cases, hair loss was imputed to multiple drugs, with 4 cases imputed to double drug combinations and 2 cases to triple combinations. Rates of severe hair loss under valproic acid (VPA) and lithium salts were distinctly lower as compared with the overall rates reported in literature. Severe hair loss under PD treatment was reported significantly more often in female patients than in male patients (p < 0.01). CONCLUSION: The rate of severe PD-related hair loss was very low in the present survey. The large number of patients included in this multicentre study allows for assessment and comparison of hair loss rates related to different PDs and groups of PDs and provides new and supplementary information on PD-related hair loss.
EVALuna2:36385

Severe parkinsonism under treatment with antipsychotic drugs - Druschky, Katrin; Bleich, Stefan; Grohmann, Renate; Engel, Rolf R.; Toto, Sermin; Neyazi, Alexandra; Däubl, Barbara; Stübner, Susanne (European archives of psychiatry and clinical neuroscience, 2019)
The aim of the study was to assess rates of severe parkinsonism related to different antipsychotic drugs (APDs) using data from an observational pharmacovigilance programme in German-speaking countries—Arzneimittelsicherheit in der Psychiatrie (AMSP). Data on APD utilization and reports of severe APD-induced parkinsonism were collected in 99 psychiatric hospitals in Austria, Germany and Switzerland during the period 2001–2016. Of 340,099 patients under surveillance, 245,958 patients were treated with APDs for the main indications of schizophrenic disorders, depression, mania and organic mental disorders. A total of 200 events of severe APD-induced parkinsonism were identified (0.08%). First-generation low-potency APDs were significantly less often implicated (0.02%) than second-generation APDs (0.07%) and first-generation high-potency APDs (0.16%). Among the second-generation APDs, amisulpride and risperidone ranked highest. The phenothiazines were associated with significantly lower rates of severe parkinsonism (0.02%) than those of the butyrophenones (0.11%) and thioxanthenes (0.12%). In 71 cases (35.5%), more than 1 drug was considered responsible for the induction of severe parkinsonism. In 44 patients (22.0%), the symptoms were extremely severe, leading to complete immobility and/or massive complications such as pneumonia and severe injuries due to falls. Higher age (> 60 years) was associated with significantly higher rates of severe parkinsonism, as were the diagnoses of schizophrenic disorder or mania. The large number of patients included in the present survey allows for the comparison of severe parkinsonism rates related to different APD classes and single APDs. The first-generation low-potency APDs had significantly reduced risk of severe parkinsonism compared not only to high potency but also to second-generation APDs.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Adverse drug reactions; AMSP programme; Antipsychotic drugs; Psychiatric inpatients; Severe parkinsonism

Use and safety of antiepileptic drugs in psychiatric inpatients-data from the AMSP study - Druschky, Katrin; Bleich, Stefan; Grohmann, Renate; Engel, Rolf R.; Kleimann, Alexandra; Stuebner, Susanne; Greil, Waldemar; Toto, Sermin (European archives of psychiatry and clinical neuroscience, 2018)
The psychiatric utilization patterns and risks of antiepileptic drugs (AEDs) were assessed by using data from the drug safety programme Arzneimittelsicherheit in der Psychiatrie over the time period 1993-2013. In a total of 432,215 patients, the main indications for AED use were acute mania, schizoaffective disorder, and schizophrenic and organic psychoses. Valproic acid (VPA) was the most common substance across all of those groups, reaching administration rates of up to 50% since 2005, at which time carbamazepine (CBZ) administration consistently dropped below a rate of 10%. Lamotrigine (LTG) and pregabalin (PGB) increased in relevance after 2005 and 2010, respectively (with administration rates of up to 9%), whereas oxcarbazepine (OXC) was least prevalent (<3%). The mean rates of severe adverse drug reactions (ADRs) ranged from 6 cases per 1000 patients treated (VPA) to 19/1000 (OXC) and were significantly lower with treatment with VPA compared to OXC and CBZ. Hyponatremia was the leading ADR during treatment with OXC; severe allergic skin reactions were most often observed during treatment with CBZ and LTG, and severe oedema was most common during treatment with PGB. Severe hyponatremia induced by OXC was observed significantly more often in female patients than in male patients.
EVALuna2:36358